Sports Play - Lapage, Ginny (Collins Educational ltd, 1990)
This work argues that sports participation is best described as a form of human play, and the attraction for participants and viewers alike derives from both its aesthetic richness and narrative structure.
Keywords: General; Sports And Recreation